The role of mundane resistance in the spectacular failure of the smart home - Murray Goulden; Lewis Cameron (Big Data & Society)
A decade on from the launch of Amazon's Alexa – the smart home's breakout product – the vision of semi-automated, pervasively sensed domesticity remains unrealised; industry losses are mounting; and big tech protagonists are in partial or full retreat from their smart home ambitions. Simultaneously, scholars draw attention to the dangers posed by the extractive business model underpinning this instantiation of the internet of things, in terms such as ‘data colonialism’, and call for an organised ‘unmaking’ of it. Against this backdrop, drawing on a 2 year study of six families living with smart home technologies (SHTs), we invoke the concept of ‘mundane resistance’, to describe the ways in which SHTs come to be diminished, or outright rejected, not by a singular user, but in the interplay of multiple members of the home in the course of their everyday participation in its moral economy. The outcome of these exchanges is a surveillance capitalism less panoptic than myopic. At a moment in time when the global economy is increasingly geared around the promis e of generative AI, recognising the potential for such uncoordinated everyday acts to, in aggregate, disassemble the grand plans of the tech industry, is of considerable value. It serves both as a rejection of the industry's grandiose self-mythologising and as a statement of the ongoing importance of attending to the situated practices of everyday life, both in its repeating patterns and its quotidian idiosyncrasies.